Pengembangan Sistem Informasi Koperasi Sekolah - Paulus, Paulus; Hanes, Hanes; Salim, Rin Rin Meilani; Cheong, Audrie Maylatasya; Garren, Codi; Lukita, Marco (Fakultas Informatika, 2025)
Besides providing education, schools also play a crucial role in addressing students' learning needs through school cooperatives. These cooperatives sell various products: stationery, uniforms, and other learning materials. Observations took place at a school in Medan with approximately 4,300 students. The school cooperative administrators face several challenges that necessitate digitization. These challenges include delays in service during peak times, reliance on Microsoft Excel sheets for data processing — rather complex and prone to reliability issues — and the burdensome sale of printed books before the new academic year, which strains the cooperative administrators and other school departments. In response to these issues, a desktop-based application and a website were developed using the Rapid Application Development (RAD) methodology. The desktop application, constructed using the C# programming language within the Windows Forms .NET Framework, is designed to streamline the cooperative's daily operational activities. The website, developed with Next.js and Node.js, incorporates web services and real-time virtual bank account payment features. These digital solutions enable cooperative administrators to manage products, purchases, sales, report generation, and online transactions more effectively and efficiently, thus resolving the identified challenges.